Bank financing and credit rationing of Australian SMEs. (February 2017) - McCarthy, Scott; Oliver, Barry; Verreynne, Martie-Louise
This paper investigates two aspects of bank financing using a sample of 1, 973 Australian small to medium sized enterprises (SMEs). We compare the variables that explain why Australian small to medium sized enterprises seek bank finance with those that underpin bank credit rationing of loan applications. Our analysis highlights that little overlap exists between the two sets of variables. Larger small to medium sized enterprises with growth intentions, business plans, and those in the agriculture industry are significantly more likely to seek finance. In contrast, firms in agriculture that are older, and that have incremental product innovation, 40% or more of export sales, and a male Chief Executive Officer, are less likely to be credit rationed. Importantly, having business plans, whether in large or small firms, does not relate significantly to credit rationing.